1989
DOI: 10.1007/bf01806549
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast sarcoma: A review of 33 cases with immunohistochemistry and prognostic factors

Abstract: The clinical and pathological features of 33 previously untreated patients with primary breast sarcoma were retrospectively analysed to evaluate the prognostic significance of histologic variables on survival. The series comprised 17 cystosarcomas phyllodes and 16 stromal sarcomas (excluding angiosarcomas). All tumors were reviewed and classified in similar fashion to extramammary soft tissue sarcomas. In addition, immunohistochemical studies were performed on paraffin sections with a panel of several antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
1
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 26 publications
3
59
1
2
Order By: Relevance
“…Reported series in the English literature had included all three entities as breast sarcomas, and include in their reports angiosarcomas, desmoid tumours, and lymphosarcomas (Botham et al, 1958;Berg et al, 1962;Oberman, 1965;Donegan, 1967;Fawcett, 1967;Kennedy and Biggart, 1967;Norris and Taylor, 1968;Rissanen and Holsti, 1968;Gogas et al, 1976;Barnes and Pietruszka, 1977;Ludgate et al, 1977;Khanna et al, 1981;Callery et al, 1985;Christensen et al, 1988;Stanley et al, 1988;Terrier et al, 1989;Pollard et al, 1990;Pitts et al, 1991;Ciatto et al, 1992;Luna Vega et al, 1992;Johnstone et al, 1993;Smola et al, 1993;Gutman et al, 1994;McGregor et al, 1994;Moore and Kinne, 1996;North et al, 1998;Barrow et al, 1999;McGowan et al, 2000). Therefore, reliable assessments of prognostic factors are difficult to make based on the published literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported series in the English literature had included all three entities as breast sarcomas, and include in their reports angiosarcomas, desmoid tumours, and lymphosarcomas (Botham et al, 1958;Berg et al, 1962;Oberman, 1965;Donegan, 1967;Fawcett, 1967;Kennedy and Biggart, 1967;Norris and Taylor, 1968;Rissanen and Holsti, 1968;Gogas et al, 1976;Barnes and Pietruszka, 1977;Ludgate et al, 1977;Khanna et al, 1981;Callery et al, 1985;Christensen et al, 1988;Stanley et al, 1988;Terrier et al, 1989;Pollard et al, 1990;Pitts et al, 1991;Ciatto et al, 1992;Luna Vega et al, 1992;Johnstone et al, 1993;Smola et al, 1993;Gutman et al, 1994;McGregor et al, 1994;Moore and Kinne, 1996;North et al, 1998;Barrow et al, 1999;McGowan et al, 2000). Therefore, reliable assessments of prognostic factors are difficult to make based on the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Berg et al defined stromal sarcomas of the breast in 1962 as a group of mesenchymal malignant tumours with fibrous, myxoid and adipose components, excluding malignant cystosarcoma phyllodes, lymphomas and angiosarcomas (Berg et al, 1962). However, series in the literature have included many different entities under the rubric of sarcomas such as cystosarcoma phyllodes, lymphosarcoma and carcinosarcoma (Botham et al, 1958;Donegan, 1967;Fawcett, 1967;Kennedy and Biggart, 1967;Rissanen and Holsti, 1968;Gogas et al, 1976;Ludgate et al, 1977;Khanna et al, 1981;Christensen et al, 1988;Terrier et al, 1989;Pitts et al, 1991;Ciatto et al, 1992;Luna Vega et al, 1992;McGregor et al, 1994;Moore and Kinne, 1996;McGowan et al, 2000). For this review, we choose to categorise primary breast sarcomas in histogenic terms, similar to other soft-tissue sarcomas, thus including angiosarcomas, and excluding malignant cystosarcomas phyllodes, as reported by others (see Table 1) (Berg et al, 1962;Oberman, 1965;Norris and Taylor, 1968;Barnes and Pietruszka, 1977;Callery et al, 1985;Stanley et al, 1988;Pollard et al, 1990;Johnstone et al, 1993;Smola et al, 1993;Gutman et al, 1994;North et al, 1998;Barrow et al, 1999).…”
mentioning
confidence: 99%
“…1 Terrier et al, in his study of 33 cases of sarcoma of breast only 2 cases of fibrosarcoma were reported. 2 Blanchard et al, in his study of 55 cases of sarcoma only 2 cases of fibrosarcoma were reported.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3] They arise from mesenchymal tissues of the breast. The annual incidence is about 44.8 new cases per 10 million women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation